Combined time-resolved laser fluorescence spectroscopy and extended X-ray absorption fine structure spectroscopy study on the complexation of trivalent actinides with chloride at T = 25-200 °C - Skerencak-Frech, Andrej; Fröhlich, Daniel R.; Rothe, Jörg; Dardenne, Kathy; Panak, Petra (Inorganic chemistry, 2014)
The complexation of trivalent actinides (An(III)) with chloride is studied in the temperature range from 25 to 200 °C by spectroscopic methods. Time-resolved laser fluorescence spectroscopy (TRLFS) is applied to determine the thermodynamic data of Cm(III)-Cl- complexes, while extended X-ray absorption fine structure spectroscopy (EXAFS) is used to determine the structural data of the respective Am(III) complexes. The experiments are performed in a custom-built high-temperature cell which is modified for the respective spectroscopic technique. The TRLFS results show that at 25 °C the speciation is dominated mainly by the Cm3+ aquo ion. Only a minor fraction of the CmCl2+ complex is present in solution. As the temperature increases, the fraction of this species decreases further. Simultaneously, the fraction of the CmCl2+ complex increases strongly with the temperature. Also, the CmCl3 complex is formed to a minor extent at T > 160 °C. The conditional stability constant log β′2 is determined as a function of the temperature and extrapolated to zero ionic strength with the specific ion interaction theory approach. The log β°2(T) values increase by more than 3 orders of magnitude in the studied temperature range. The temperature dependency of log β°2 is fitted by the extended van’t Hoff equation to determine ΔrH°m, ΔrS°m, and ΔrC°p,m. The EXAFS results support these findings. The results confirm the absence of americium(III) chloride complexes at T = 25 and 90 °C ([Am(III)] = 10-3 m, [Cl-] = 3.0 m), and the spectra are described by 9-10 oxygen atoms at a distance of 2.44-2.48 Å. At T = 200 °C two chloride ligands are present in the inner coordination sphere of Am(III) at a distance of 2.78 Å.
Gesehen am 28.10.2020